(untitled) (Eurasian Scientific Herald, 2023)
The functionality and effectiveness of the complex of psychological, pedagogical and organizational and pedagogical conditions proposed in this article in the process of teaching a foreign language to students in various situations, their verbal understanding, assessment, expression, regulation with a focus on development and increasing communicative competence as an integral element of professional training in a pedagogical university, in order to significantly increase educational motivation, to contribute to the professional development of the future teacher